Seven years of brexit: Economic geographies of regional de- and recoupling. Editorial - Johannes Glückler; Dariusz Wójcik (ZFW - Advances in Economic Geography, 2023)
This editorial offers a comprehensive introduction to the economic geographies of Brexit. It reviews the state of research on the multiple causes and consequences of the 2016 UK referendum and highlights the role of geographical context in the way that these factors interact in affecting voting behaviour and economic impact. Departing from an appraisal of the literature, we discuss the scope of six original studies collected in the special issue that, each using different analytical methods, present evidence on the impact of Brexit on the relocation of financial services firms, the recoupling of London with the other European financial centres, differences in regional productivity across the UK, as well as on the potential of UK regional policy to offset the disadvantages of financial decoupling from the European Union. Recognizing signs of political and economic disintegration beyond Europe, we conclude by highlighting a need for further research on the economic geographies of de- and recoupling.
Keywords: 330; Brexit; economic geography; Impact Assessment; regional policy; relocation